Building an entrepreneurship model in Indonesia’s electric vehicle industry: struggling or sustaining - Haryanto, Antonius Rainier; Hamsal, Mohammad; Abdinagoro, Sri Bramantoro; Rahim, Rano Kartono (Frontiers in Sustainability, 2026)
The introduction of electric vehicles as a solution for the Indonesian government to reach a net-zero carbon target by 2060 has led to the formation of new ventures by both established and new entrepreneurs, focusing on electric vehicle products or support services. Although these ventures align with and are supported by various government policies, they still face challenges in thriving and sustaining themselves within the Indonesian automotive market. Recognizing this challenge, this study aims to understand key variables that influence a company’s ability to survive, known as organizational resilience, in the dynamic automotive industry. The research used a qualitative method, combining a systematic literature review on electric vehicle entrepreneurship with semi-structured interviews. Based on an analysis of 40 key papers related to electric vehicle entrepreneurship published between 2021 and 2025 and semi-structured purposive interviews with ten electric vehicle industry business leaders in Indonesia conducted between July and August 2024, the study developed a theoretical research model proposing five theoretical propositions. The model comprises three independent variables that contribute to organizational resilience: entrepreneurial orientation within the organization, organizational leadership agility, and the organization’s commitment to environmental sustainability. The model also includes two perceived variables: entrepreneurial orientation as the mediating factor and government policy as the moderating factor. This research advances the Dynamic Capabilities theory by providing insights, especially on how environmental sustainability orientation and business model innovation influence organizational resilience. Given the cross-sectional qualitative approach focusing on Indonesia, this study has limitations, and future research, particularly with empirical methods, is recommended to further validate these findings.